The unheard scream : reproductive health and women's lives in India - Rao, Mohan (Zubaan : Panos Institute, India, 2004)
The International conference on population and development (ICPD) at Cairo brought about a "paradigm shift" in the way population is conceptualized. This involves going beyond material health and family planning to the broader framework of reproductive health and rights. How has India fared with the paradigm shift? Is this about population control by other means? Is it about the social roots of illness, disease and death among women? This revelatory collection of essays by journalists explores a range of issues from the quinacrine sterilization scandal to the rip off that is the assisted reproduction industry to the declining age of marriage among Muslim girls in Malabar. Winners of the panos reproductive health media fellowship these journalists reveal how issues in women’s health are deeply imbricated in the lives of Indian women.